Connecting informal and formal learning experiences in the age of participatory media - Bull, Glen; Thompson, Ann; Searson, Mike; Garofalo, Joe; Park, John; TYoung, Carl; Lee, John (Contemporary issues in technology and teacher educationContemporary issues in technology and teacher education, 2008)
The renaissance stimulated by the World Wide Web is generating multiple formats and channels of communication and creativity. The Pew Internet and American Life project reports that the majority of all teens are now engaged in active creation of online content. The rise of social media reflects new opportunities and outlets for creativity. Increased youth engagement through these activities represents a repurposing of what Clay Shirky terms a cognitive surplus . Shirky believes that a movement from passive activities such as watching television to more active and creative pursuits is emerging as a use of the cognitive surplus in the Web 2.0 era. Collaborative projects such as Wikipedia demonstrate that a previously unexploited collective intelligence can be tapped when the right conditions are established. This study is about new projects and processes with new media.
Keywords: internet; jeunesse; médias sociaux